2021
DOI: 10.1111/jcpe.13438
|View full text |Cite
|
Sign up to set email alerts
|

Flapless application of enamel matrix derivative in periodontal retreatment: A multicentre randomized feasibility trial

Abstract: Subgingival instrumentation is an effective approach during initial periodontal therapy directed at the suppression/elimination of the subgingival bacterial load. Clinical endpoints of treatment that are usually assessed at re-evaluation after this first phase of therapy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 40 publications
5
40
0
Order By: Relevance
“…The enhanced pocket reduction and pocket closure observed in this study coincides with the results of adjunctive EMD application during initial non‐surgical therapy (Schallhorn et al, 2020) and re‐instrumentation of residual pockets persisting after steps 1 and 2 of periodontal therapy (Jentsch et al, 2021). Graziani et al (2019) also stated that a higher number of cases with no residual PPD ≥6 mm was observed with EMD application at 3 months.…”
Section: Discussionsupporting
confidence: 86%
“…The enhanced pocket reduction and pocket closure observed in this study coincides with the results of adjunctive EMD application during initial non‐surgical therapy (Schallhorn et al, 2020) and re‐instrumentation of residual pockets persisting after steps 1 and 2 of periodontal therapy (Jentsch et al, 2021). Graziani et al (2019) also stated that a higher number of cases with no residual PPD ≥6 mm was observed with EMD application at 3 months.…”
Section: Discussionsupporting
confidence: 86%
“…When EMD was very recently evaluated for the nonsurgical treatment of residual pockets, even though in the study it was concluded that the results obtained were statistically better than SI alone, the percentage of shallow pockets (PPD ≤ 4 mm) obtained by EMD and HA at 6 months was 89% and 76%, respectively; meanwhile, at 12 months it was 80% and 77%, respectively [ 47 ]. Concerning the endpoint of therapy (PPD ≤ 4 mm without BOP), at 6 months, EMD and HA could obtain 69% and 58%, respectively, while at 12 months they could obtain 80% and 59%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics of the included studies are shown in Table 1. Eight of the included studies were randomized clinical trials 22–25,30–33 : two of them were multi‐centre studies with one of them being conducted in the United States, Canada and Germany 24 and the other one in Germany and Italy 23 . The included articles were published between 2003 and 2021, and patients' recruitment was completed in private, 22,24 university 25 or both private and university dental clinics 23 .…”
Section: Resultsmentioning
confidence: 99%
“…The included articles were published between 2003 and 2021, and patients' recruitment was completed in private, 22,24 university 25 or both private and university dental clinics 23 . The included number of patients in each study population ranged from 12 32 to 49 24 and the majority of the studies included both smokers and non‐smokers 22–25,30–33 . The treatment outcome following non‐surgical periodontal treatment + EMD (SRP + EMD) and non‐surgical periodontal treatment alone or placebo (SRP alone or placebo) was assessed for a period of 3–12 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation